(untitled) (Revista Contexto & Educação, 2022)
This article, based on the socio-historical-cultural theoretical perspective, promotes a critical discussion about the inclusion of children with disabilities from the perspective of teachers and trainees in the Pedagogy course. It aims to trigger reflection on the senses and meanings attributed to the presence of a trainee at an inclusive classroom. It uses selected examples from a research corpus collected at a municipal school in São Paulo, extracted from a 2019 master’s dissertation, which will support the discussion supported by Vygotsky ([1924] 1997; 1930; [1930] 2008; [1930] 2010 ; [1934] 2001). The results point to a critical review and reflection on the trainees in an inclusive classroom.